2013
DOI: 10.1371/journal.pone.0065880
|View full text |Cite
|
Sign up to set email alerts
|

Application of Holistic Liquid Chromatography-High Resolution Mass Spectrometry Based Urinary Metabolomics for Prostate Cancer Detection and Biomarker Discovery

Abstract: Human exhibit wide variations in their metabolic profiles because of differences in genetic factors, diet and lifestyle. Therefore in order to detect metabolic differences between individuals robust analytical methods are required. A protocol was produced based on the use of Liquid Chromatography- High Resolution Mass Spectrometry (LC-HRMS) in combination with orthogonal Hydrophilic Interaction (HILIC) and Reversed Phase (RP) liquid chromatography methods for the analysis of the urinary metabolome, which was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 37 publications
0
50
0
Order By: Relevance
“…developed their signatures in blood samples, and it is of note that there was little crossover in terms of the specific constituent metabolites with the urine-based diagnostic signatures proposed by Zhang et al . (38), Struck-Lewick et al (42) or Wu et al . (36).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…developed their signatures in blood samples, and it is of note that there was little crossover in terms of the specific constituent metabolites with the urine-based diagnostic signatures proposed by Zhang et al . (38), Struck-Lewick et al (42) or Wu et al . (36).…”
Section: Resultsmentioning
confidence: 99%
“…The selected studies indicated that distinct clusters based on metabolite profiles could be identified in a variety of biological media including blood (40, 41, 51), urine (36, 38, 42), tissue (16, 28, 31, 32, 45, 47, 52) and expressed prostatic secretions (39). These clusters were able to distinguish cancer from benign (28, 31, 32, 36, 38-42, 47), tumors by their degree of aggressiveness (16, 32, 47), cases who recurred (45), and those who responded well to therapy (51).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, the combination of reversed-phase and hydrophilic interaction liquid chromatography (HILIC) is also an interesting strategy, since the coupling HILIC-MS allows analyzing polar compounds in biological samples without the recourse of the derivatization step needed in gas chromatography [4][5][6]. Alternatively, capillary electrophoresis (CE) can also resolve the polar metabolome, but its combination with RP-LC-MS has only been proposed in a few works [7][8].…”
Section: Graphical Abstractmentioning
confidence: 99%
“…The field of lipidomics has evolved to fill this gap and lower abundance metabolites are analyzed in more specialized assays such as those described for estrogens [3]. Cancer metabolic studies are generally conducted using either NMR spectroscopy or LC-MS using three major approaches: first, untargeted LC-MS methods to profile metabolites in order to discover those that are dysregulated using sophisticated software packages to reveal differences in the chromatographic profiles [47]. Characterizing the differentially regulated metabolites that are found remains a major challenge.…”
mentioning
confidence: 99%